Pandemics, society, and public health, 1517-1925. - National Archives (Great Britain); British Library; University College, London; London Metropolitan Archives (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2024)
Charting the history of pandemics over five centuries, Pandemics, Society, and Public Health, 1517-1925, collates archival materials relating primarily to the history of the UK. The collection concentrates on four diseases that have left a particularly significant mark on British history: plague, cholera, smallpox, and influenza. This collection boasts over 500 documents, meticulously sourced from four leading archives across the United Kingdom: the British Library, the National Archives, University College London, and London Metropolitan Archives. Carefully curated along thematic lines, these primary resources are grouped together under a series of topics, formulated specially to reflect the needs and interests of our users.
Date range: 1517-1925.
Keywords: Pandemics -- Great Britain -- History; Pandemics -- Social aspects -- Great Britain; Public health -- Great Britain -- History; Plague -- Great Britain -- History; Cholera -- Great Britain -- History; Smallpox -- Great Britain -- History; Influena -- Great Britain -- History